2008
DOI: 10.1002/jnr.21883
|View full text |Cite
|
Sign up to set email alerts
|

Guanosine improves motor behavior, reduces apoptosis, and stimulates neurogenesis in rats with parkinsonism

Abstract: Parkinson's disease (PD) is characterized by progressive degeneration of dopaminergic neurons in the substantia nigra pars compacta (SNc) caused by an abnormal rate of apoptosis. Endogenous stem cells in the adult mammalian brain indicate an innate potential for regeneration and possible resource for neuroregeneration in PD. We previously showed that guanosine prevents apoptosis even when administered 48 hr after the toxin 1-methyl-4-phenylpyridinium (MPP(+)). Here, we induced parkinsonism in rats with a prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 58 publications
1
38
0
Order By: Relevance
“…In this in vivo model of parkinsonism, a functional improvement (i.e., decrease in motor dysfunction) was detected in rats chronically treated with guanosine [38]. In addition to a reduction in apoptosis induced by this purine, this study also found that guanosine treatment caused an increase in the number of dopaminergic neurons in the substantia nigra as well as cell proliferation in the subventricular zone (SVZ).…”
Section: Protective Effects Of Guanosine In Neurodegenerative Diseasessupporting
confidence: 50%
See 3 more Smart Citations
“…In this in vivo model of parkinsonism, a functional improvement (i.e., decrease in motor dysfunction) was detected in rats chronically treated with guanosine [38]. In addition to a reduction in apoptosis induced by this purine, this study also found that guanosine treatment caused an increase in the number of dopaminergic neurons in the substantia nigra as well as cell proliferation in the subventricular zone (SVZ).…”
Section: Protective Effects Of Guanosine In Neurodegenerative Diseasessupporting
confidence: 50%
“…We found that guanosine has antidepressant-like effects in these behavioral tests, decreasing the immobility time of mice in both the TST and the FST [173]. This effect was observed at doses (0.05-5 mg/kg, administered orally) lower than those commonly used in in vivo studies that have assessed its neuroprotective efficacy (around 8 mg/kg) [38,96,148]. Moreover, the use of specific pharmacological inhibitors suggested that these behavioral effects were dependent on the activation of the PI3K/Akt signaling pathway, as well as its downstream target mammalian target of rapamycin (mTOR) [173], an important regulator of protein synthesis that has been implicated in synaptogenesis and fast-acting antidepressant responses [174].…”
Section: Protective Effects Of Guanosine In Mood Disordersmentioning
confidence: 73%
See 2 more Smart Citations
“…administration of guanosine increased the amounts of both guanosine and guanine in the spinal cord, with a peak around 30 min [50]. Considering that extracellular guanine also exerts several biological effects [51,52], it is tempting to propose that some biological effects of guanosine may be regulated by its conversion to guanine by a membrane located purine nucleoside phosphorylase.…”
Section: Synthesis and Metabolism Of Guanine-based Purinesmentioning
confidence: 99%